Gate stress reliability of a novel trench-based Triple Gate Transistor. (November 2021) - Gay, R.; Marca, V. Della; Aziza, H.; Laine, P.; Regnier, A.; Niel, S.; Marzaki, A.
Abstract: This paper addresses the reliability on a novel trench-based Triple Gate Transistor (TGT) fabricated in a 40 nm embedded Non-Volatile Memory (e-NVM) technology. In the studied device, two vertical transistors are integrated in deep trenches alongside the main planar transistor to build a TGT. The reliability of this device is investigated targeting the gate oxide degradation, that represents one of the major reliability issues in e-NVM environment. Gate stress tests are motivated by the possibility to use independently trench transistors and the main planar transistor. Thus, the reliability of each gate oxide needs to be studied separately to the others. Moreover, different DC and AC stress tests are performed and analysed to understand the degradation mechanisms effecting the TGT device. Highlights: A novel trench based triple gate transistor architecture Architecture fabricated in a 40 nm embedded Non-Volatile Memory technology Structure composed of one planar gate and two vertical trench gates Gate stress reliability in AC and DC mode on this structure